Below are listed several pairs of sentences, both in propositional logic and in predicate logic. In each pair, one of the sentences implies the other. Decide which of the two logically implies the other one, and give justification for your answer.
(a) Q; P ⇒ Q
(b) S ∧ (P ⇒ Q) ∧ ((¬P) ⇒ Q); Q ∨ R
(c) ∀y ∃x R(x, y); ∃x ∀y R(x, y)
(d) (∀x P(x)) ⇒ (∃x P(x)); ∀x (P(x) ⇒ Q(x))
(e) (∀x P(x)) ∨ (∀x ¬P(x)); (∃x P(x)) ⇒ (∀x P(x))
I tried to approach each of these using reasoning rather than truth tables. But I must admit it ended up being more of a guessing game than anything. So I need some help.
For a), I thought that Q implies P ⇒ Q because when in some cases when P ⇒ Q is true, Q is still false.
For b), I thought Q ∨ R implies S ∧ (P ⇒ Q) ∧ ((¬P) ⇒ Q) because Q is present in the larger statement and R is not so I thought the smaller statement could just be considered as Q only.
For c), I thought ∀y ∃x R(x, y) implies ∃x ∀y R(x, y) because I thought that if all x existed for all y, then there would be an x for all y.
For d), I thought ∀x (P(x) ⇒ Q(x)) implies(∀x P(x)) ⇒ (∃x P(x)) because when P(x) exists for all x, then it exists regardless of Q(x).
For e), I thought (∃x P(x)) ⇒ (∀x P(x)) implies (∀x P(x)) ∨ (∀x ¬P(x)) because P(x) either exists or doesn't depending on x.
However, my reasoning is not very strong for either.
Any help?
(a) Q; P ⇒ Q
(b) S ∧ (P ⇒ Q) ∧ ((¬P) ⇒ Q); Q ∨ R
(c) ∀y ∃x R(x, y); ∃x ∀y R(x, y)
(d) (∀x P(x)) ⇒ (∃x P(x)); ∀x (P(x) ⇒ Q(x))
(e) (∀x P(x)) ∨ (∀x ¬P(x)); (∃x P(x)) ⇒ (∀x P(x))
I tried to approach each of these using reasoning rather than truth tables. But I must admit it ended up being more of a guessing game than anything. So I need some help.
For a), I thought that Q implies P ⇒ Q because when in some cases when P ⇒ Q is true, Q is still false.
For b), I thought Q ∨ R implies S ∧ (P ⇒ Q) ∧ ((¬P) ⇒ Q) because Q is present in the larger statement and R is not so I thought the smaller statement could just be considered as Q only.
For c), I thought ∀y ∃x R(x, y) implies ∃x ∀y R(x, y) because I thought that if all x existed for all y, then there would be an x for all y.
For d), I thought ∀x (P(x) ⇒ Q(x)) implies(∀x P(x)) ⇒ (∃x P(x)) because when P(x) exists for all x, then it exists regardless of Q(x).
For e), I thought (∃x P(x)) ⇒ (∀x P(x)) implies (∀x P(x)) ∨ (∀x ¬P(x)) because P(x) either exists or doesn't depending on x.
However, my reasoning is not very strong for either.
Any help?